Adult Neural Stem Cells: Born to Last - Morales, Aixa V.; Mira, Helena (Frontiers in Cell and Developmental Biology, 2019)
The generation of new neurons is a lifelong process in many vertebrate species that provides an extra level of plasticity to several brain circuits. Frequently, neurogenesis in the adult brain is considered a continuation of earlier developmental processes as it relies in the persistence of neural stem cells, similar to radial glia, known as radial glia-like cells (RGLs). However, adult RGLs are not just leftovers of progenitors that remain in hidden niches in the brain after development has finished. Rather, they seem to be specified and set aside at specific times and places during embryonic and postnatal development. The adult RGLs present several cellular and molecular properties that differ from those observed in developmental radial glial cells such as an extended cell cycle length, acquisition of a quiescence state, a more restricted multipotency and distinct transcriptomic programs underlying those cellular processes. In this minireview, we will discuss the recent attempts to determine how, when and where are the adult RGLs specified.